2020
DOI: 10.1093/ofid/ofaa018
|View full text |Cite
|
Sign up to set email alerts
|

Multiple NDM-5-Expressing Escherichia Coli Isolates From an Immunocompromised Pediatric Host

Abstract: Background Genes conferring carbapenem resistance have disseminated worldwide among Gram-negative bacteria. Here we present longitudinal changes in clinically obtained Escherichia coli isolates from 1 immunocompromised pediatric patient. This report demonstrates potential for antibiotic resistance genes and plasmids to emerge over time in clinical isolates from patients receiving intensive anticancer chemotherapy and broad-spectrum antibiotics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Although NDM producers have been recently detected in a single patient in Lisbon [ 18 ], no bla NDM-1 was found in gulls in our study, suggesting its still low diffusion rate. While ST940 was the predominant E. coli background identified from gulls in our study, this ST had not been identified in Portugal before and, to the best of our knowledge, has been exclusively identified among NDM-5-producing E. coli isolates in the US [ 36 ]. By contrast, the K. pneumoniae ST17 background that has frequently been identified here is a clonal type frequently found among clinical isolates recovered from Portuguese patients [ 24 ].…”
Section: Discussionmentioning
confidence: 76%
“…Although NDM producers have been recently detected in a single patient in Lisbon [ 18 ], no bla NDM-1 was found in gulls in our study, suggesting its still low diffusion rate. While ST940 was the predominant E. coli background identified from gulls in our study, this ST had not been identified in Portugal before and, to the best of our knowledge, has been exclusively identified among NDM-5-producing E. coli isolates in the US [ 36 ]. By contrast, the K. pneumoniae ST17 background that has frequently been identified here is a clonal type frequently found among clinical isolates recovered from Portuguese patients [ 24 ].…”
Section: Discussionmentioning
confidence: 76%
“…In contrast to NDM-1 that is widely spread among several Enterobacterales and other Gram-negative bacilli, NDM-5 seems to be more restricted to Escherichia coli isolates ( Wu et al., 2019 ), as it was the first to be reported from a patient in the United Kingdom after previous hospitalization in India ( Hornsey et al., 2011 ). In the Americas, NDM-5 has been only described in clinical isolates in the USA ( Mediavilla et al., 2016 ; Flerlage et al., 2020 ) and, to the best of our knowledge; it has not been reported in human clinical samples in Latin America, so far. We are aware that the emergence of a novel variant in our geographical region could lead to the replacement or substitution of the prevailing carbapenemases present in the area.…”
Section: Introductionmentioning
confidence: 83%
“…To date, E. coli isolates belonging to ST940 have been sporadically reported. The first E. coli ST940 isolates reported harbored the bla NDM-5 gene, encoded on IncX3 and IncFII plasmids, and caused invasive infection in an immunocompromised pediatric patient hospitalized in 2014 in Lebanon and later transferred to the USA [ 17 ]. ST940 has been also found in Ghana, in E. coli carrying the bla OXA-181 gene localized on an IncFIC plasmid [ 18 ], and it has been recently reported as the predominant clone among uropathogenic E. coli isolates in India [ 19 ].…”
Section: Resultsmentioning
confidence: 99%